Cultural Literacy in Teaching English for Guiding - Made Aryawan Adijaya (Universitas Pendidikan Ganesha, 2023)
Cultural literacy is highly needed by those who deal with tourism area as the subject of the study. English for Guiding is one of the courses that belongs to Diploma 3 English of Ganesha University of Education and it deals with tourism. This study aims at discussing the need analysis of cultural literacy in teaching English for guiding in order to know about cultural components involved in the teaching process. This study is descriptive study which describe about the need of the students in cultural literacy. The data were gathered through questionnaires to gain the information about the cultural elements in cultural literacy that can support the students in learning English for Guiding and prepare them to become skillful in English proficiency as well as competent and knowledgable in contents. The data were gathered by using questionnaire in order to gain the information about the students’ need on the cultural literacy in lerning English for guiding. The finding shows that there are seven big cultural elements such as 1) symbols; 2) language; 3) norms; 4) rituals; 5) changing norms and belief; 6) values which provide the consideration of what is good and bad, desirable and undesirable; 7) artifacts. The implications of this research are hoped that in the future students will be able to be professional and competent through cultural literacyg.